A new variant of superficial lipomatosus nevus: a case report - Trisno, Anggreini O.; Tan, Sukmawati T.; Wellen, Fendy (International Journal of Research in Dermatology, 2025)
Superficial lipomatosus nevus, or nevus lipomatosus superficialis (NLS), is a benign skin hamartoma characterized by ectopic deposition of mature adipose tissue within the dermis. NLS is a rare type of hamartoma with two clinical forms, namely the classical (multiple) and the solitary type. Diagnosis of NLS requires histopathological examination to confirm its features. Therefore, this study aimed to report a case of a new variant of NLS in a 50-year-old female patient who had an enlarging and troublesome patch on the right side of the neck for the past three years, and was unresponsive to previous treatments. Dermatological examination showed a well-defined macule, measuring 6×3 cm, with erythema, a brownish color, an active edge, and no scaling. Laboratory test results were within normal limits. Initially, the lesion was suspected to be superficial basal cell carcinoma (BCC). The patient was subjected to excision, and histopathology results confirmed NLS. An excision was then carried out to remove the lesion.